One stone two birds: anti-inflammatory bronchodilators as a potential pharmacological strategy for COVID-19 - Yu, Yuanyuan; Fang, Bangjiang; Yang, Xiao-Dong; Zheng, Yuejuan (Frontiers in Pharmacology, 2023)
The ongoing Coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has imposed a huge threat to public health across the world. While vaccinations are essential for reducing virus transmission and attenuating disease severity, the nature of high mutation rate of SARS-CoV-2 renders vaccines less effective, urging quick development of effective therapies for COVID-19 disease. However, developing novel drugs remains extremely challenging due to the lengthy process and high cost. Alternatively, repurposing of existing drugs on the market represents a rapid and safe strategy for combating COVID-19 pandemic. Bronchodilators are first line drugs for inflammatory lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Compared to other anti-inflammatory drugs repurposed for COVID-19, bronchodilators are unique in that they have both anti-inflammatory and bronchodilating properties. Whether the dual properties of bronchodilators empower them greater potential to be repurposed for COVID-19 is worth exploring. In fact, clinical and preclinical studies have recently emerged to investigate the benefits of bronchodilators such assalbutamol, formoterol and theophylline in treating COVID-19, and many of them have shown encouraging efficacy on attenuating disease severity of pneumonia and other associated symptoms. To comprehensively understand the latest progress on COVID-19 intervention with bronchodilators, this review will summarize recent findings in this area and highlight the promising clinical benefits and possible adverse effects of bronchodilators as therapeutic options for COVID-19 with a focus on β2 receptor agonists, anticholinergic drugs and theophylline.